Off the books : a novel - Frazier, Soma Mei Sheng (Henry Holt and Company, 2024)
"A captivating debut following a cross-country road trip that will make you believe in the goodness of people, Off the Books sheds light on the power in humanity during the most troubled of times. Recent Dartmouth dropout Mei, in search of a new direction in life, drives a limo to make ends meet. Her grandfather convinces her to allow her customers to pay under the table, and before she knows it, she is working as a routine chauffeur for sex workers. Mei does her best to mind her own business, but her knack for discretion soon leads her on a life changing trip from San Francisco to Syracuse with a new client. Handsome and reserved, Henry piques Mei's interest. Toting an enormous black suitcase with him everywhere he goes, he's more concerned with taking frequent breaks than making good time on the road. When Mei discovers Henry's secret, she does away with her usual close-lipped demeaner and decides she has no choice but to confront him. What Henry reveals rocks her to her core and shifts this once casual, transactional road trip to one of moral stakes and dangerous consequences. An original take on the great American road trip, Off the Books is a beautifully crafted coming of age story that showcases the resilience of the human spirit and the power of doing the right thing. The spirit of Frazier's characters will stay with readers long after they have arrived at their destination"--